Linguistic-discursive strategies of comic representation of death in television advertising - Palacios, Annamaria da Rocha Jatobá (2015)
The paper aims to understand the use of humor by advertising when announces products and services and connect themselves with the symbolic universe about death. The purpose is to understand the linguistic-discursive strategies present in TV advertising presenting death as main subject. The analysis is founded on assumptions of semantic theories and theoretical postulates identified as belonging to the fields of pragmatic-language. Specific contributions of sociological, anthropological and philosophical assist in understanding of the Western historical legacy of death. This exploratory analysis of a set of television advertisements, it indicates that in spite of the seriousness of death, the use as a central theme in the advertising accounts contributes to breaking the current supremacy of sex as recurrently used element by institutionalized socio- discursive practices.